Environmental law for transitions to sustainability - Boeve, M. N. (Marlon N.); Akerboom, Sanne; Backes, Chr.; Van Rijswick, Marleen (Cambridge : Intersentia, 2021)
This book presents inspiring ideas about how law can support the fundamental transition processes to a sustainable future and how it can provide guidance on the pathways to sustainability.
Title from publisher's bibliographic system (viewed on 11 Nov 2021).
Keywords: Environmental law -- Congresses; Sustainable development -- Law and legislation -- Congresses